Analisis Perbandingan Biaya Pembangunan Rumah Layak Huni Dengan Metode Konvensional Dan Ferosemen Di Kota Kupang Nusa Tenggara Timur - Firdaus, Nor Aidi; Veronika Happy Puspasari (Jurnal Basement : Jurnal Teknik Sipil, 2023)
In Indonesia, there is still extreme poverty caused by several factors, one of which is low-income among the population. The President of the Republic of Indonesia for the 2019-2024 period, Mr. Joko Widodo, conveyed Presidential Instruction No. 4 of 2022, stating that the Ministry of Public Works and Housing needs to support the acceleration of eradicating extreme poverty, one of which is by improving inadequate housing into habitable dwellings. The implementation of this activity refers to Circular Letter No. 3/SE/Dr/2021 on technical instructions for conducting self-help housing stimulus activities (BSPS). BSPS is a government aid program for low-income communities to encourage and enhance self-reliance in improving housing quality through conventional and ferrocement methods. The purpose of this research is to obtain a cost comparison of habitable dwellings using conventional and ferrocement methods for types 27, 36, and 39 houses. Descriptive analysis methods were employed to determine the budget design for habitable dwellings using conventional and ferrocement methods based on unit price work analysis. Data for this research was obtained from the implementation of BSPS in 2022. The results of the cost comparison analysis for habitable dwellings using conventional and ferrocement methods showed that the budget for a conventional type 27 house amounted to Rp. 345,549,510.48, while the ferrocement house required Rp. 242,127,415.19. For a conventional type 36 house, the budget needed was Rp. 390,354,427.82, while the ferrocement house required Rp. 274,401,749.21. Lastly, for a conventional type 39 house, the budget needed was Rp. 455,467,373.11, while the ferrocement house required Rp. 313,893,235.77.